MODIFIED THREE-DIMENSIONAL CLASSIFICATION OF THE ADOLESCENT IDIOPATHIC SCOLIOSIS - Enguer Beraldo Garcia; Gabriel António de Matos; Carlos Eduardo de Oliveira Senna; Liliane Faria Garcia; André de Sá; Enguer Beraldo Garcia Júnior; Juliana Garcia Camarinha; Victor de Oliveira Matos; Juliano Chaves (Coluna/Columna)
ABSTRACT Objective: This study aims to present the modifications to the Modified Three-Dimensional Classification (MTC) and show the results of its use in the classification of radiographic images of the spine of four hundred and four patients who underwent surgery for Adolescent Idiopathic Scoliosis (AIS). Method: MTC was used to classify the radiographic images of the spine of four hundred and four patients who had undergone surgery for AIS. A panoramic X-ray of the spine was performed in the orthostatic position, in the lateral and anterior pos-teroanterior views, neutral and with forced inclination to the right and left. The results of the classification variables and the relevant patient data were collected from the medical records and a biostatistical study was carried out. The MTC is made up of three factors: quantitative, localizing and sagittal. Results: A higher incidence of double curve scoliosis was observed. The main curve predominated in the distal thoracic region. The sagittal plane showed a higher incidence of normal angle. There was a higher incidence of hyperlordosis in females. There was a predominance of hypokyphosis in younger individuals. The results tables show that these predominances occurred with significant differences. Conclusion: The study of the MTC variables applied to the classification of patients undergoing AIS surgery showed a three-dimensional scope, and therefore concludes a truly three-dimensional classification. Level of Evidence III; Retrospective Study.